Quem tem mói e quem não tem não vai moer: reflexões sobre o período do pós-guerra do contestado no Alto Vale do Rio do Peixe (1920-1940) - Pereira, Douglas Henrique (2020)
This dissertation deals about the process of colonization of the region “Alto Vale do Rio do Peixe” after the War of the Contestado, occured in this place. In search of answers and evidences that prove the relationship between the War of the Contestado, the process of colonization realized in the sequence of the conflict and the situation of poverty found nowadays in the region, several sources were examined and a vast academic production about on this theme. The time frame was fixed in the period between 1920-1940, a period in which the negotiations were intensified for the colonization of the region “Alto Vale do Rio do Peixe” The action of the colonizers companies is fundamental in this understanding, as well as the attitudes and actions of the various spheres of public authorities, and for that were examined conversations, messages, reports and official studies produced about the colonization of the region, when they demonstrated a social exclusion to the ancient residents of the region in consequence of to the arrival of the migrants and immigrants of European descent. Today, the region “Alto Vale do Rio do Peixe” has the lowest socioeconomic data in the state of Santa Catarina, and in its history are the answers to this situation.